FEMALE LEADERS CREATING STEPPING LADDERS: Exercising Strategic Agency in Religiously Affiliated Universities of Indonesia and the USA - Wardatun, Atun; Haeri, Shahla; Nurjanah, Siti (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
This article aims to draw on the lessons and experiences of female leaders for what approaches should be nurtured and adopted in breaking the ‘glass ceilings.’ This research examines pathways to female leadership and public acceptance of their roles. The article offers strategies for the next generation of emerging female leaders, drawing from narratives of five female leaders in five religiously affiliated universities in Indonesia and three in the United States. This article argues that an intense external discourse could expedite the internal institutional force of change for female university leaders. A collective solidarity among professional peers is pivotal for women to reach leadership positions, however the institutional force must be sustained with a conducive social and political support. The ‘stepping ladders’ illustrate how women’s tracking to the leadership roles and building up a path to advance the chances remained a critical challenge, as exercising an ultimate command under the shadow of patriarchal can complicate the question of who is the true leader? The research contributes to widen the vision of what female leadership in the universities have advanced, highlighting the external and internal influence that entrenched and nurtured such development. These influences should be adaptable and structured to response to the critical call to reach the quantity and quality of female leadership to advance authority and agency contexts.[Abstrak: Artikel ini bertujuan untuk mengambil pembelajaran dan pengalaman para pemimpin perempuan mengenai pendekatan apa yang harus dikembangkan dan diterapkan dalam mendobrak ‘langit-langit kaca’. Penelitian ini mengkaji jalur kepemimpinan perempuan dan penerimaan masyarakat terhadap peran mereka. Artikel ini menawarkan strategi untuk generasi pemimpin perempuan masa depan, yang diambil dari lima narasi pemimpin perempuan di lima universitas berafiliasi keagamaan di Indonesia dan tiga di Amerika Serikat. Artikel ini berargumentasi bahwa wacana eksternal yang intens dapat mempercepat perubahan kekuatan institusional internal bagi para pemimpin perempuan di universitas. Solidaritas kolektif di antara rekan-rekan profesional sangat penting bagi perempuan untuk mencapai posisi kepemimpinan. Kekuatan kelembagaan harus ditopang dengan dukungan sosial dan politik yang kondusif. ‘Tangga loncatan’ ini menggambarkan bagaimana upaya perempuan dalam mencapai peran kepemimpinan dan membangun jalur untuk meningkatkan peluang, masih menjadi tantangan, dimana menjalankan peran kepemimpinan tetapi berada di bawah bayang-bayang patriarki dapat mempersulit dalam menjawab pertanyaan tentang siapakah pemimpin yang sebenarnya? Penelitian ini berkontribusi untuk memperluas visi mengenai kemajuan yang dicapai oleh kepemimpinan perempuan di universitas, dengan menyoroti pengaruh eksternal dan internal yang memperkuat dan memupuk perkembangan tersebut. Pengaruh-pengaruh ini harus dapat disesuaikan dan lebih terstruktur demi menanggapi tuntutan penting untuk mencapai kepemimpinan perempuan baik secara jumlah dan kualitas guna memajukan konteks otoritas dan lembaga.]